OPTIMIZATION OF EXPERIMENTAL INDUSTRIAL TECHNOLOGY OF SILICON-CONTAINING DERIVATIVES OF POLYOL SUBSTANCES PRODUCTION - A. A. Boyko; S. V. Mordanov; T. G. Khonina; O. N. Chupahin (Разработка и регистрация лекарственных средств, 2019)
The process of the synthesis of silicon-containing glycerol derivatives of Si(С3H7O3)4 ∙ 6С3Н8O3  composition was optimized on the example of creation of the experimental industrial technology of the drug substance «Silativit» production. The main criterion of optimization was reducing a time and energy expenditure on carrying out the synthesis, representing heterophase reaction of alcoholysis of initial alkoxysilane by polyol. Optimization was performed on such indicators of process as temperature condition, the mode of removal of an easily volatile product of reaction, the mode of mixture of reactionary weight and type of the used mixing device.